A GPSG Appraisal of Sequential Distribution of Auxiliary Verbs in Ìjesà Dialect of Yorùbà (Nordic Journal of African Studies, 2003)
The structural distribution of the auxiliary verbs in Ìjesà dialect of Yorùbá is highlighted in this paper. The description is carried out within the framework of Generalised Phrase Structure Grammar (GPSG) as promulgated by Gazdar et al. (1985). The analysis of the sequential co-occurrence of the auxiliary verbs demonstrated in this study does not fail to take into cognizance the structural relevance of the variants of these auxiliary verbs. The paper further discusses a comparative study of the markers of the auxiliary verbs in Ìjesà and Standard Yorùbá.